2021
DOI: 10.1002/cam4.3860
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CDKN2A homozygous deletion in combination with methylated MGMT status for IDH‐wildtype glioblastoma

Abstract: Objective Accumulating evidence from recent molecular diagnostic studies has indicated the prognostic significance of various genetic markers for patients with glioblastoma (GBM). To evaluate the impact of such genetic markers on prognosis, we retrospectively analyzed the outcomes of patients with IDH‐wildtype GBM in our institution. In addition, to assess the impact of bevacizumab (BEV) treatment, we compared overall survival (OS) between the pre‐ and post‐BEV eras. Methods We analyzed the data of 100 adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…McDonald's standard was created based on the WHO oncology response criteria, which is a general diagnostic imaging standard for solid tumors [ 33 ]; therefore, the measurement protocol for contrast-enhancement lesions has not been changed for more than 20 years. Our results propose the possibility that some patients evaluated as SD by the RANO criteria may have a good prognosis and suggest an alternative threshold value for identifying the group with a good prognosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…McDonald's standard was created based on the WHO oncology response criteria, which is a general diagnostic imaging standard for solid tumors [ 33 ]; therefore, the measurement protocol for contrast-enhancement lesions has not been changed for more than 20 years. Our results propose the possibility that some patients evaluated as SD by the RANO criteria may have a good prognosis and suggest an alternative threshold value for identifying the group with a good prognosis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, univariate analysis for molecular markers revealed an unmethylated MGMT status, and CDKN2A homozygous deletion showed a trend toward poor prognosis. Our recent study also reported that MGMT and CDKN2A status could stratify Japanese GBM patients into three race-specific groups with different prognoses [ 26 ]. Further accumulation of studies including molecular-genetic signatures and evidence beyond real-clinic data are warranted to evaluate the significance of image changes during BEV-included regimens for unresectable GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional molecular alterations have been associated with prognostic relevance in glioblastoma, although results are less than unanimous. CDKN2A/B loss has been linked with reduced overall survival; however, some studies have found this to be true only in tumors without MGMT methylation [76,77]. Recent work has also demonstrated variable associations between TERT mutation and unfavorable clinical course [77,78].…”
Section: Gl Iobl a Stom A I Dh -W I L Dt Y Pementioning
confidence: 99%
“…D2-0217; MRC Holland, Amsterdam, The Netherlands) according to our previous study. 22 As a result, TP53 and NFKBIA deletions were detected (Fig. 4).…”
Section: Genetic Findingsmentioning
confidence: 95%